Islamic English in Islamic talks - Othman, Khairiah; Ismail, Anis Izzati (EDP Sciences, 2018)
The international nature of the English language has affected many communities across the globe and this has led to the emergence of varieties of English, specifically to meet the needs of non-native speakers of English. For Muslim speakers, Islamic English has been proposed which aims to maintain Arabic terms in the English language when there is an absence of equivalent English words. An attempt to translate would lead to distortion in meanings. This paper aims to highlight the presence of Islamic English employed by an international prominent Islamic speaker. Content analysis method is employed. The findings indicate the functions of Islamic English in the speaker’s talks are to provide the accurate meaning of the terms, correct misconceptions and lack of equivalent word in the English language, hence the need for Islamic English for Muslim speakers of English.